Genes Implicated in Rare Congenital Inner Ear and Cochleovestibular Nerve Malformations. Issue 4 (July 2020) - Kari, Elina; Llaci, Lorida; Go, John L.; Naymik, Marcus; Knowles, James A.; Leal, Suzanne M.; Rangasamy, Sampath; Huentelman, Matthew J.; Liang, Winnie; Friedman, Rick A.; Schrauwen, Isabelle
Abstract : Objective: A small subset of children with congenital hearing loss have abnormal cochleovestibular nerves (i.e., absent, aplastic, or deficient cochlear nerves), with largely unknown etiology. Our objective was to investigate the underlying pathways and identify novel genetic variants responsible for cochleovestibular malformations and nerve abnormalities. It is our hypothesis that several cochleovestibular nerve abnormalities might share common causative pathways. Design: We used a family-based exome sequencing approach to study 12 children with known rare inner ear and/or cochleovestibular nerve malformations. Results: Our results highlight a diverse molecular etiology and suggest that genes important in the developing otic vesicle and cranial neural crest, e.g., MASP1, GREB1L, SIX1, TAF1, are likely to underlie inner ear and/or cochleovestibular nerve malformations. Conclusions: We show that several cochleovestibular nerve malformations are neurocristopathies, which is consistent with the fact that cochleovestibular nerve development is based on otic placode-derived neurons in close association with neural crest-derived glia cells. In addition, we suggest potential genetic markers for more severely affected phenotypes, which may help prognosticate individual cochlear implantation outcomes. Developing better strategies for identifying which children with abnormal nerves will benefit from a cochlear implantation is crucial, as outcomes are usually far less robust and extremely variable in this population, and current neuroimaging and electrophysiologic parameters cannot accurately predict outcomes. Identification of a suitable treatment early will reduce the use of multiple interventions during the time-sensitive period for language development. Abstract : Supplemental Digital Content is available in the text.